Examining Rural Transformation in Gisting, Tanggamus Regency, Lampung Province - Muhammad Dzaky Al Murthado (The Indonesian Journal of Planning and Development, 2023)
Rural transformation is often triggered by urbanization, which is marked by changes in the economic structure, land use, and population dynamics. This transformation can lead to both development opportunities and challenges, including agricultural decline, land-use conflicts, and environmental degradation. This study examines rural transformation in the Gisting Subdistrict, Tanggamus Regency, Lampung Province, which has experienced a shift from a predominantly agricultural area to a more urbanized setting. Between 2000 and 2010, five villages in Gisting, changed status from rural to urban, as classified by BPS (2010). This research aims to measure the degree of rural transformation and identify the key internal and external factors influencing the process. Using a quantitative approach, the degree of transformation was assessed using indicators of population, land use, and industry. Regression analysis was used to determine the most influential factors. Internal factors include economic, social, and resource variables, while external factors are based on the transformation levels of nearby sub-districts. Data sources include household surveys and secondary data from the BPS and various government agencies. The findings indicate that Gisting experienced a high degree of rural transformation in 2010, 2015, and 2020. The most influential internal factors were per capita GRDP and water availability. Externally, the transformation processes in Kota Agung and Talang Padang significantly impact Gisting. These results offer insight into the formulation of sustainable rural development strategies in the region.